Writing the literature review for empirical papers - Nakano, Davi; Muniz Jr., Jorge (Associação Brasileira de Engenharia de Produção, 2018)
AbstractPaper aims The purpose of the paper is to offer guidance regarding how to write a Literature Review for empirical papers, that provides adequate background and convincing support. The literature review plays the fundamental role of unveiling the theory, or theories, that underpin the paper argument, sets its limits, and defines and clarifies the main concepts that will be used in the empirical sections of the text.Originality Most papers and books focus on literature review as full articles (systematic reviews, meta analyses and critical analyses) or dissertation, chapters, this paper is focused on literature review for an empirical article.Research method It is a theoretical essay.Main findings The paper summarizes the main steps for performing a literature review and guides how to organize the analyzed literature.Implications for theory and practice Well-crafted literature reviews are the cornerstone of good papers, and this paper offers some guidance on how to write good reviews for empirical papers, and, as a consequence, to produce better quality texts.
Keywords: Literature review; Metanalyses; Critical analyses; Empirical paper